Therapeutic immunization strategies for the control of HIV-1. - Dorrell, L (2005)
Highly active antiretroviral therapy (HAART) is currently the only means to halt or prevent progression to AIDS. However, lack of access to medications for the vast majority of HIV-1-infected individuals in immediate need, together with the requirement for lifelong adherence and potential for serious toxicity, are significant limitations which have yet to be overcome. Augmentation of HIV-specific immunity by therapeutic vaccination is being explored as a possible alternative to continuous HAART. A few candidate HIV-1 vaccines have entered clinical trials involving an assessment of viremia control during an analytic therapy interruption, but even the most promising of these achieve a short-lived suppression of HIV-1 without HAART. Nevertheless, these studies are guiding the development of better immune augmentation strategies, which could extend the time off therapy and will also contribute to a better understanding of the immune correlates of protection against AIDS. The status of therapeutic vaccines that are currently undergoing preclinical and clinical evaluation is reviewed.